Kształtowanie wtórnego habitusu przez szkolne rytuały - Dembiński, Mariusz (Studia Edukacyjne, 2020)
The purpose of the article is an attempt to develop the primary habitus into the secondary in school environment, through the passage rituals (rites de passage) and related to them social drama (Social Drama). I assume that the school environment is normalized by institutionalized rituals in which the primary habitus is transformed into the secondary habitus through rituals. Its subjective consolidation and possible transformation is being done by education and upbringing. From the side of education, consolidation and transformation are complemented by school documentary and textual practices, and from the side of education by the moral ideal, conditioned by so-called the effect of reversing. All this process, hermeneutically and circularly complements the structure of the rite of passage.